1999
DOI: 10.1023/a:1020511002025
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We characterized the cytokine profile in the liver of patients with primary biliary cirrhosis (PBC). Total RNA was extracted from the biopsy specimens of 9 patients with early-stage PBC, 10 with chronic hepatitis C (CHC), and 4 normal controls. cDNA was prepared and amplified with a polymerase chain reaction using primers for interferon (IFN)-gamma and interleukin (IL)-2, -4, -5, -6, -10, -12 (p40), and -15. Cytokines such as IFN-gamma and IL-5, -6, -10, -12, and -15 were expressed in most cases of PBC. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…The monocyte PAMP-induced cytokine production observed in our study appears compatible with previously obtained data [76][77][78][79][80], which implicate a significant role of Th-1 cytokines in the pathogenesis of PBC. We note, however, that Th-2 cytokines, such as IL-5, IL-6, and IL-10 have also been detected in PBC livers [77,79], thus indicating that both Th-1 and Th-2 cytokines, possibly during different stages of the disease, might be involved in the pathogenesis of PBC. A longitudinal study will therefore be necessary to evaluate whether the observed differences are secondary to other mechanisms that contribute to the pathogenesis of PBC.…”
Section: Monocytessupporting
confidence: 92%
“…The monocyte PAMP-induced cytokine production observed in our study appears compatible with previously obtained data [76][77][78][79][80], which implicate a significant role of Th-1 cytokines in the pathogenesis of PBC. We note, however, that Th-2 cytokines, such as IL-5, IL-6, and IL-10 have also been detected in PBC livers [77,79], thus indicating that both Th-1 and Th-2 cytokines, possibly during different stages of the disease, might be involved in the pathogenesis of PBC. A longitudinal study will therefore be necessary to evaluate whether the observed differences are secondary to other mechanisms that contribute to the pathogenesis of PBC.…”
Section: Monocytessupporting
confidence: 92%
“…Cytokine expression in the liver of primary biliary cirrhosis patients is similarly mixed. Compared to other liver diseases, increased hepatic expression of IL-5, IL-6, IFNγ, TGFβ, and IL-2 has been noted (257, 258). Recent studies also identified key Th1 and Th17 cytokines in the liver (259) and on blood cells (260) and a decreased T regulatory to Th17 cell balance in peripheral blood cells (261).…”
Section: Role Of Eosinophils In Autoimmune Diseasesmentioning
confidence: 99%
“…Eosinophil infiltration is higher in the early stages of the disease (stages I–II versus III–IV) (263, 265). Increased eosinophil infiltration was positively associated with liver IL-5 expression (258) and mast cell infiltration (264). Infiltrating eosinophils are degranulating, releasing ECP, MBP, and EDN, which can also be detected in the serum (262, 265).…”
Section: Role Of Eosinophils In Autoimmune Diseasesmentioning
confidence: 99%
“…Analysis of RNA expression in explanted PBC liver samples has consistently revealed skewing of the cytokine profile with reduced IL-10 (a predominantly Th2 cytokine) and increased interferon gamma (IFNγ; a Th1 cytokine) in comparison to chronic hepatitis C explants [16], [17]. Levels of serum IL-18 – which acts to release IL-12 and activate the Th1 pathway – and IFNγ are also elevated in PBC patients relative to levels detected in healthy controls and chronic viral hepatitis patients [18], [19].…”
Section: Introductionmentioning
confidence: 99%